Pengaruh Kualitas Pelayanan, Kualitas Produk dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi Pada Haidee Rental Malang) - Alfiah Said (STIE Kertanegara Malang, 2023)
Haidee Rental is a solution for parents to provide quality baby and child equipment at affordable prices. Haidee Rental not only rents out children's toys but also rents out necessities for mothers who have just given birth. This study aims to determine the effect of customer satisfaction, product quality and customer satisfaction on customer loyalty simultaneously where in the analysis process it is known that there is a positive influence between service quality, product quality and customer satisfaction on customer loyalty at Haidee Rental Malang simultaneously and only customer satisfaction. on customer loyalty which has a partial negative effect.. Keywords— Customer Satisfaction, Product Quality, Customer Satisfaction, Customer Loyalty